Description of a new species in the genus Bythotrephes Leydig, 1860 (Crustacea: Cladocera: Onychopoda), supplements to selected species, and concluding remarks on the genus - Korovchinsky, Nikolai M. (Zootaxa, 2020)
A new species of the genus Bythotrephes is described based on material collected in the mountain lakes of Tyva Republic (Southern Siberia, Russia). The representatives of the new species are especially close to those of B. longimanus having long tl I, straight caudal process, and only two pairs of claws on postabdomen and caudal process, respectively. At the same time, the new species is, on average, smaller with shorter caudal process and fairly long apical setae of second endopodital segment of the thoracic limbs of first pair (tl I). Supplemental data on morphology, taxonomy, and geographic distribution of other species of the genus, e.g., B. arcticus, B. cederströmii, B. brevimanus, and B. lilljeborgi, are presented. For B. cederströmii, in particular, females of first generation hatched from resting eggs are described for the first time. Classification of the genus is discussed and an updated key for species and a hybrid form is presented. The highest species richness of the genus, observed within the Scandinavian Peninsula and in the north of European Russia, may indicate the central region of primary speciation which generally coincides with the region of the last Quaternary maximum glaciation. The isolated occurrence of three species, B. longimanus, B. transcaucasicus, and B. centralasiaticus sp. nov. on the southern border of the genus’ range, in pre-Alpine and mountain lakes of Europe, Transcaucasia, and Southern Siberia (Tyva) and isolated localities of B. arcticus in Northern Kazakhstan, could also be due to the effect of glaciation(s). Regarding the origin of the genus Bythotrephes, it is hypothesized that it occurred in pre-Pleistocene time in the ancient Ponto-Caspian basin, experiencing large-scale transgressions, where the intensive radiation of ancestral Onychopoda probably took place.